New alien and invasive bamboo aphid species of the genus Takecallis (Hemiptera: Aphididae) recorded in Poland – morphological and molecular identity - Karina Wieczorek; Kaja Ball; Roma Durak; Beata Borowiak-Sobkowiak (Journal of Plant Protection Research, 2024)
The occurrence of three bamboo aphid species of the genus Takecallis was detected. T. arundicolens (Clarke) and T. arundinariae (Essig) were recorded for the first time in Poland, and new localities for T. nigroantennatus Wieczorek were found. Key diagnostic morphological characteristics to help distinguish these species and DNA barcoding to analyze individuals at the molecular level were provided.